The otter trawl fishing of North-Eastern Panay. - Depante, Jaime H. (Miagao Iloilo College of Fisheries, University of the Philippines, 1951)
The Philippines, as a fishing country, is very rich in fishery resources. The coastline totaled 11, 444 miles, twice as long as the coastline of the United States and is surrounded by about 705, 000 sq. miles of territorial sea water. The total land area is 115, 036 sq. miles which is just about 6 1/2 the size of total territorial sea water. It is composed of about 7,000 islands, big and small, whose coastline are intended by numerous gulfs, bays, coves and rivers and provided with shallow reefs and open seas of varying depths, There are almost 2, 000 species of fish of varying sizes from other aquatic products such as crabs, oysters, turtles, corals, sponges, etc. encountered in these waters. So extensive are the territorial waters of the Philippines and vast are its aquatic resources that the fishing industry is regarded as the third, if not the second, basic country of the Philippines. A million people are directly dependent upon it. The industry is not limited to one place alone, this being the source of livelihood by people throughout the country. It is a known fact that the chief food of the Filipino people consist of rice and fish. Since time immemorial, the people kept themselves supplied with sea food to fill, in a large measure, the protein requirement of their diet rice and fish. The methods of procuring these particular food have been developed by themselves with equipment rigged out of materials produce from local sources and operated largely with bare hands. These fishing methods, though efficaciously applied have been recognized as being inadequate and incapable of supplying sufficient qualities of fish for the nation's population. Because of the crude and ineffective ways of taking fish, the fishermen of the whole country could not satisfy the people's great demand for fish and other fishery products, so that variations in their ways of taking fish were introduced. These variations, together with other modernized fishing methods introduced by foreign country greatly helped supply the country with more fish, which is a vital necessity in our economic progress during the last war. The effect of the destruction of records, facilities and equipments has been tremendous and expansion of the industry was greatly retarded. The great havoc caused by the last war put our fishing industry into a sad state. After the termination of the last war, the Filipino people, still undaunted, valiantly resumed its fishing activities to produce at least the minimum requirements of this very important protein food in their primary diet of rice and fish. The people of America easily recognized the fact that the fishing industries occupy a very important position in the country's economy. As a result they did not hesitate to enact laws to enable to United States Government to assist us in overcoming some of the difficulties we encountered in the rehabilitation of our fisheries and to lay the background for the program activities leading to the modernization of this basic industry of the Philippines. Among the modern methods of catching fish introduced by the Americans, the otter trawl was found to be the most suitable and profitable so that at present, this method of fish capture occupies first place in our ways of catching fish. The otter trawl is used on waters throughout the Philippines, notably in Northeastern Panay where an abundance of fish prevails. Before the introduction of the otter trawl and the beam trawl, fishing activities were carried on a small scale. The methods used by fishermen for catching fish were mostly by means of Basnig and on a much smaller scale, the handline and the pole and line. Despite the richness of our fishing grounds, the fisherman cannot cope with the demands of the population for the sole reason that their methods of catching fish could not bring sufficient fish supply for the people's consumption. During that time dynamitting was quite rampant on these parts because of the great quantity of fish caught in this nefarious operation. However, after the introduction of the otter and beam trawl, notably the former, dynamitting has diminished considerably because of the bright prospect promised by these gears and since more otter trawls are being built at present, dynamiters will soon find employment in this profitable enterprise without fear of getting apprehended for illegal fishing.
Keywords: Fish-Capture.